PENGARUH METODE GAME APLIKASI KAHOOT TERHADAP KEMAMPUAN LITERASI BAHASA INDONESIA SISWA KELAS V SEKOLAH DASAR (Template-Jurnal-Pendas) - Fajar Nugroho, Nanda; Sri Maruti, Endang; Prima Yudhaningtyas, Sesaria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesian language literacy skills of fifth grade students at SDN Jiwan 02 were relatively low due to monotonous learning methods that relied heavily on worksheets and textbooks, causing students to be less active and easily bored. This study aims to determine the effect of the Kahoot game application method on Indonesian language literacy skills of fifth grade students at SDN Jiwan 02. The research employed a Pre-Experimental Design with a quantitative approach using a one-group pretest-posttest design. The research subjects were all 19 fifth grade students of SDN Jiwan 02, selected using cluster random sampling. The research instrument consisted of 20 multiple-choice questions, with 16 items declared valid and reliable (Cronbach's Alpha = 0.981). Data were analyzed using the Shapiro-Wilk normality test and the Paired Sample T-Test. The normality test results indicated that both pretest and posttest data were normally distributed (Sig. > 0.05). The hypothesis test results showed a two-sided p-value < 0.001, thus H₀ was rejected and H₁ was accepted. Therefore, there is a significant effect of using the Kahoot game application method on Indonesian language literacy skills of fifth grade students at SDN Jiwan 02.